Scientific argumentation and deliberative democracy: an incompatible mix in school science? - Erduran, S; Kaya, E (Taylor and Francis (Routledge), 2016)
The article investigates how deliberative democracy is related to argumentation in school science. We use examples of political models of deliberative democracy to synthesize implications for argumentation in science teaching and learning. Some key questions guided our approach: How does democratic deliberation work and how does it relate to scientific argumentation? How might the principles and practices of deliberative democracy be used to facilitate scientific argumentation in science lessons? Are democratic values consistent or in conflict with scientific practices that demand an emphasis on particular evidence and justifications? To address these questions, we present practical pedagogical examples that illustrate the overlap and the tensions in argumentation in relation to deliberative democracy in the scientific context.